Rol del modelo MEST en la percepción de la realidad sobre el estado de los recursos hídricos en ingeniera civil (2016)
The studies of this article were made based on the designs and data calculated on the bridge “Guillermo Gaviria Correa” that crosses the Magdalena river. The goal is to show that all the civil works are designed to last “certain number of years” and not really to resist certain forces. The MEST model is a good example because it shows us the world as it really should be, testing all our senses in order to conclude which is the most important way that gives the largest amount of information to the brain by means of stimulations. The present work is a product of the research project PIC 1382, developed by the research group “Vision Colombia Hídrica” de la Universidad Militar Nueva Granada.